ITI 2008 - 30th International Conference on Information Technology Interfaces 2008
DOI: 10.1109/iti.2008.4588446
|View full text |Cite
|
Sign up to set email alerts
|

Modeling prehensile actions for the evaluation of Tangible User Interfaces

Abstract: Abstract. Prehension, or reaching-to-grasp is a very common movement performed by users of Tangible User Interfaces (TUIs) because through this movement users can manipulate tangible artifacts. Here we present an experiment that provides evidence towards the hypothesis that prehensile movements can be modeled based on the amplitude of the prehension movement. We then explore consequences of this evidence on the modeling and evaluation of TUIs using tools that can predict task completion times, such as Goals, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…L. MacKenzie & Iberall, 1994). Thus, we developed a prehension operator (Christou, Ritter, & Jacob, 2008) and used it to calculate a prediction for the prehension action. Second, GOMSL cannot compute the completion time of 540 the method "Find Required File" because there are no primitive operators defined for the steps of this method and because of its iterative nature.…”
Section: Construction Of the Goms Models Gomsl Was Chosen From The Vamentioning
confidence: 99%
“…L. MacKenzie & Iberall, 1994). Thus, we developed a prehension operator (Christou, Ritter, & Jacob, 2008) and used it to calculate a prediction for the prehension action. Second, GOMSL cannot compute the completion time of 540 the method "Find Required File" because there are no primitive operators defined for the steps of this method and because of its iterative nature.…”
Section: Construction Of the Goms Models Gomsl Was Chosen From The Vamentioning
confidence: 99%
“…Previous studies have demonstrated only weak to moderate strength models of prehension using Fitts' law, and recent work has even focused on finding a better model for complex tasks. Christou, Ritter, and Jacob (2008) have provided evidence that an exponential model, using only the movement distance variable, may be more appropriate for modeling prehensile movements. Future studies are needed to explicitly investigate the utility of other such models in the design of 3D TUIs.…”
Section: Models Of Prehension For Physical Collaboration In Virtual Ementioning
confidence: 99%